The Use of The Adventure by Angels & Airwaves as Authentic Material in EFL Vocabulary and Critical Thinking Instruction - Afif Zuhdy Idham; Nurul Hasbi; Arfah Hamzah (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
This study investigates the integration of alternative rock poetics as authentic instructional material to enhance advanced vocabulary acquisition and higher-order thinking skills (HOTS) among tertiary EFL students. Utilizing a qualitative case study design, this research examined an intact cohort of fourth-semester pre-service English teachers (N = 28) at Universitas Muhammadiyah Barru during the 2025/2026 academic year. The pedagogical intervention was framed around Angels & Airwaves’ metaphor-dense track "The Adventure," operationalized via a Task-Based Language Teaching (TBLT) model. Data collection was triangulated through classroom observations, student analytical portfolios, and semi-structured interviews. Thematic analysis revealed that the song's complex lexical layers successfully pushed students past literal definitions into metaphorical decoding. Furthermore, navigating the semiotic tension between the song’s optimistic auditory composition and its isolating visual aesthetics served as a robust catalyst for critical interpretation and evaluation. The study concludes with practical implications for EFL practitioners to counter AI-induced cognitive passivity by exploiting multimodal popular culture.